CO2‐water‐rock interactions in undeformed and sheared claystone caprocks from Northern Europe. Issue 2 (10th December 2020) - Vernooij, Roland; Siqueira, Tiago de Abreu; Hangx, Suzanne; Spiers, Christopher; Ketzer, Marcelo; Iglesias, Rodrigo Sebastian
Abstract: One of the most promising, cost‐effective, and readily available technologies for reducing greenhouse gas emissions to the atmosphere is the capture and separation of CO2 from large stationary sources and storage in geological formations. Storage security, especially in the early stages of operation, is mostly guaranteed by caprock formations with very low permeability overlying the reservoir, capable of containing the injected fluid. Chemical alterations of the formation brine, caused by CO2 injection may cause dissolution and precipitation of secondary minerals, potentially increasing the risks of leakage from the reservoir. In order to evaluate these processes and their potential to induce the formation of leakage pathways in ultrafine fault gouges, a series of batch experiments was performed on crushed and sheared samples from three different caprock formations from Northern Europe (Sollingen, Röt and Opalinus claystones). The experiments were supported by numerical models of the kinetics of mineral dissolution and precipitation simulating the same experimental conditions, and over a longer time (10 000 years). Minor mineral alterations were observed after the batch experiments, the most important being: illite dissolution for the Opalinus and Röt formation samples, and dolomite dissolution and the transformation of illite and chlorite into kaolinite for the Sollingen sample. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd.